Cytologic-Radiologic Correlation Using Transthoracic CT-Guided FNA for Lung and Mediastinal Masses: Our Experience. (2014) - Piplani, Sanjay; Mannan, Rahul; Lalit, Monika; Manjari, Mridu; Bhasin, Tejinder S.; Bawa, Jasmin
Abstract : Background and Objectives. Thoracic lesions account for various benign and malignant conditions. Of these lung carcinoma (mainly primary) is the most common carcinoma in the world. The present study was undertaken to know the pathological spectrum of thoracic lesions and to correlate cytoradiological findings. Materials and Methods. The present study was conducted in a tertiary care center of North India on 74 patients over an 18-month period. CT guided transthoracic FNAC (TTFNA) was carried out, and aspirates were drawn, examined, and compared with radiological diagnoses. Results. The diagnostic accuracy for FNA in the present study was calculated to be 95.94% (using cytology as the gold standard). The predominant lesion was malignancy (85.1%), followed by suspicions of malignancy and inflammatory pathology (5.40% each). By cytology, the most common malignant lesion was adenocarcinoma (48%) followed by squamous cell carcinoma (40%), small cell carcinoma (8%), and undifferentiated carcinoma (4%). Cytoradiological correlation was found to be 89.2% in the present study. Conclusion. Present study thus concludes that TT FNA of thoracic lesions is a simple, safe, economically prudent technique associated with low morbidity and leading to quick and early diagnosis.